The Influence of Job Satisfaction, Organizational Commitment and Coworker Support on Organizational Citizenship Behavior among Private Sector Employees - Astrid Ayu Rahma Putri; Ignatius Soni Kurniawan; Tri Ratna Purnamarini (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Organizational Citizenship Behavior (OCB) is voluntary behavior of employees that exceeds formal job requirements and plays an important role in improving organizational effectiveness. In practice, private sector companies often face highly competitive work dynamics and high-performance demands, so organizations need employees who not only perform their main duties, but also demonstrate proactive, cooperative behavior and are willing to make additional contributions to the organization. This phenomenon indicates that extra-role behavior is an important factor in supporting organizational success. This study aims to analyze the influence of job satisfaction, coworker support, and organizational commitment on OCB among private sector employees in Yogyakarta. This study uses a quantitative approach with a survey method by distributing questionnaires to 43 respondents who are private sector employees in Yogyakarta. The data analysis technique used is Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that job satisfaction and organizational commitment positively affect OCB behavior, while coworker support does not have a significant effect on this behavior. These findings indicate that employees' psychological attachment to the organization and their level of job satisfaction are important factors in encouraging extra-role behavior in the work environment. The implications of this study show that organizations need to improve the quality of the work environment, strengthen organizational commitment, and create working conditions that can increase employee satisfaction so that organizational citizenship behavior can develop optimally and support the achievement of organizational goals.